The Effect of Pocket Money, Lifestyle, and Self-Control on Consumption Behavior of Muhammadiyah University Management Students Gresik Class 2018 - Chalimatus Sakdiyah; Anita Handayani (INNOVATION RESEARCH JOURNAL, 2022)
Consumptive behavior is an individual action in consuming excessively without thinking rationally and more concerned with wants than needs. The results of the pre-survey conducted by researchers show that management students of the University of Muhammadiyah Gresik class of 2018 are considered to reflect consumptive behavior and are still lacking in utilizing the pocket money they receive. This study aims to determine the effect of pocket money, lifestyle and self-control on consumptive behavior in management students at Muhammadiyah University of Gresik. The research method uses quantitative research methods with a sample of 142 respondents. The data obtained were analyzed using multiple linear regression analysis using the SPSS 16 program. The results showed that pocket money had a positive and significant effect on consumptive behavior, lifestyle had a positive and significant effect on consumptive behavior, and self-control had a negative and significant effect on consumptive behavior.